Linking the GAD-7 and PHQ-9 to the TBI-QOL Anxiety and Depression Item Banks. Issue 5 (September 2019) - Boulton, Aaron J.; Tyner, Callie E.; Choi, Seung W.; Sander, Angelle M.; Heinemann, Allen W.; Bushnik, Tamara; Chiaravalloti, Nancy; Sherer, Mark; Kisala, Pamela A.; Tulsky, David S.
Abstract : Objective: To link scores on commonly used measures of anxiety (7-item Generalized Anxiety Disorder Scale; GAD-7) and depression (9-item Patient Health Questionnaire; PHQ-9) to the Traumatic Brain Injury Quality of Life (TBI-QOL) measurement system. Setting: 5 Traumatic Brain Injury Model Systems. Participants: A total of 385 individuals with traumatic brain injury (TBI) (31% complicated mild; 14% moderate; and 54% severe). Design: Observational cohort. Main Measures: GAD-7, PHQ-9, TBI-QOL Anxiety v1.0 and TBI-QOL Depression v1.0. Results: Item response theory–based linking methods were used to create crosswalk tables that convert scores on the GAD-7 to the TBI-QOL Anxiety metric and scores on the PHQ-9 to the TBI-QOL Depression metric. Comparisons between actual and crosswalked scores suggest that the linkages were successful and are appropriate for group-level analysis. Linking functions closely mirror crosswalks between the GAD-7/PHQ-9 and the Patient-Reported Outcomes Measurement Information System (PROMIS), suggesting that general population linkages are similar to those from a TBI sample. Conclusion: Researchers and clinicians can use the crosswalk tables to transform scores on the GAD-7 and the PHQ-9 to the TBI-QOL metric for group-level analyses.